Implementasi Manajemen Mutu Terpadu di Madrasah Aliyah Negeri 1 Bandar Lampung - Nadia, Putri; Patimah, Siti; Subandi, Subandi; Junaidah, Junaidah; Ayu, Sovia Mas (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
The background of this research is the high interest of the people who are still vying to enter their children in MAN 1 Bandar Lampung, the number of new student enrollments every year has increased the number of registrants even though it doesn't look significant. However, there is an increasing number of applicants every year. This is also because many generations of student families have returned to study at MAN 1 Bandar Lampung. The purpose of this research is to explore the implementation of integrated quality management at MAN 1 Bandar Lampung. This research use desciptive qualitative approach. Data collection is done by conducting interviews, observation and documentation. Analysis of the data used in this study was carried out by reducing the data, after which it was presented in the form of a description and verified by drawing conclusions. The results of this study indicate that: The implementation of integrated quality management at MAN 1 Bandar Lampung, is already good, namely it is continuously pursued by prioritizing customer (student) satisfaction services, has involved all madrasa residents through teacher meetings every month or every two months, has an organizational structure that contains control, the head of the madrasa builds commitment by empowering all madrasa residents according to their competence and capacity to contribute to improving quality, madrasa management always makes creative efforts to satisfy students' services such as bringing in motivators.